DIGITAL IMAGE PROCESSING USING TECHNIQUES OF MATHEMATICAL MORPHOLOGY - Stroppa, Raquel Grando [UNESP]; Leonardi, Fabricio [UNESP]; Silva, Erivaldo Antonio da [UNESP]; Baralt, J.; Callaos, N.; Chu, H. W.; Ferrer, J.; Lesso, W.; Savoie, M. J. (Int Inst Informatics & Systemics, 2010)
The cartographic products of Brazil are around 30 years outdated. The present work describes an alternative to diminish this problem by using the coupling of products of Remote Sensing and techniques of mathematical morphology (MM). The images of the Remote Sensing can be considered as a source of data for studies in many areas, such as the cartography, urban planning, agriculture and environment. Such use can be justified by its rapidity, efficiency, regularity in the attainment of data and low cost. In addition, an important component is the technique of Digital Processing of Imagens (DPI). In this work it was used MM theory for extraction of draining and new calculation of the reservoir of the hydroelectric power plant, assigned Mascarenhas de Moraes, located in the Rio Grande River in Minas Gerais State, Brazil. The obtained results are promising and evidenced the great potential of mathematical morphology in the area of cartography.
Keywords: Mathematical Morphology; Cartographic Features; Update; Digital Image Processing; Remote Sensing